Contemporary management of traumatic cervical and thoracic esophageal perforation: The results of an Eastern Association for the Surgery of Trauma multi-institutional study. Issue 4 (October 2020) - Raff, Lauren A.; Schinnerer, Eric A.; Maine, Rebecca G.; Jansen, Jan; Noorbakhsh, Matthew R.; Spigel, Zachary; Campion, Eric; Coleman, Julia; Saquib, Syed; Carroll, Joseph T.; Jacobson, Lewis E.; Williams, Jamie; et al.
Abstract : BACKGROUND: Traumatic esophageal perforation is rare and associated with significant morbidity and mortality. There is substantial variability in diagnosis and treatment. Esophageal stents have been increasingly used for nontraumatic perforation; however, stenting for traumatic perforation is not yet standard of care. The purpose of this study was to evaluate current management of traumatic esophageal perforation to assess the frequency of and complications associated with esophageal stenting. METHODS: This was an Eastern Association for the Surgery of Trauma multi-institutional retrospective study from 2011 to 2016 of patients with traumatic cervical or thoracic esophageal injury admitted to one of 11 participating trauma centers. Data were collected and sent to a single institution where it was analyzed. Patient demographics, injury characteristics, initial management, complications, and patient mortality were collected. Primary outcome was mortality; secondary outcomes were initial treatment, esophageal leak, and associated complications. RESULTS: Fifty-one patients were analyzed. Esophageal injuries were cervical in 69% and thoracic in 31%. Most patients were initially managed with operative primary repair (61%), followed by no intervention (19%), esophageal stenting (10%), and wide local drainage (10%). Compared with patients who underwent operative primary repair, patients managed with esophageal stenting had an increased rate of esophageal leak (22.6% vs. 80.0%, p = 0.02). Complication rates were higher in blunt compared with penetrating mechanisms (100% vs. 31.8%, p = 0.03) despite similar Injury Severity Score and neck/chest/abdomen Abbreviated Injury Scale. Overall mortality was 9.8% and did not vary based on location of injury, mechanism of injury, or initial management. CONCLUSION: Most patients with traumatic esophageal injuries still undergo operative primary repair; this is associated with lower rates of postoperative leaks as compared with esophageal stenting. Patients who have traumatic esophageal injury may be best managed by direct repair and not esophageal stenting, although further study is needed. LEVEL OF EVIDENCE: Therapeutic, level IV.